Candidate gene molecular markers as tools for analyzing genetic susceptibility to Morbillivirus infection in stranded Cetaceans - Stejskalova, Karla; Bayerova, Zuzana; Futas, Jan; Hrazdilova, Kristyna; Klumplerova, Marie; Oppelt, Jan; Splichalova, Petra; DI GUARDO, Giovanni; Mazzariol, Sandro; DI FRANCESCO, Cristina Esmeralda; Di Francesco, Gabriella; Terracciano, Giuliana; et al. (2017)
Morbilliviruses, such as Cetacean morbillivirus (CeMV) or Phocine distemper 70 virus (PDV), represent a growing threat for marine mammals on both hemispheres. Since free-ranging animal populations strongly rely on natural resistance mechanisms, innate immunity related genes and virus cell entry receptor genes may represent key factors involved in susceptibility to CeMV in Cetaceans. Using the next generation sequencing technology, we have sequenced eleven candidate genes in two model species, Stenella coeruleoalba and Phocoena phocoena. Suitable single nucleotide polymorphism markers of potential functional importance, located in genes coding for basigin (BSG, CD147), the signaling lymphocyte activating molecule (SLAMF1), the poliovirus related receptor-4 (NECTIN4, PVRL4), toll-like receptors 3,7,8 (TLR3, TLR7, TLR8), natural resistance-associated macrophage protein (SLC11A1) and natural cytotoxicity triggering receptor 1 (NCR1), were identified in each model species, along with MHC-DQB haplotypes unique for each species. This set of molecular markers represents a potentially useful tool for studying host genetic variation and susceptibility to Morbillivirus infection in Cetaceans as well as for studying functionally important genetic diversity of selected Cetacean populations.